EVALUASI PROTEINURIA PADA PASIEN DIABETES MELITUS DENGAN KEBIASAAN MINUM TEH - Handayani, Trimar; Himawan, Fathurrozak; Prihandana, Sadar (Juru Rawat. Jurnal Update Keperawatan, 2025)
Diabetes Mellitus (DM) is a chronic metabolic disease that may lead to microvascular complication, including  diabetic nephropathy, which is characterized by proteinuria. Proteinuria serves as an early indicatot of kidney  damage in DM patients. Tea consumption patterns, particularly green and black tea, have attracted attention  due to their polyphenol content, which may provide protective effects on kidney function. This study aimed to  evaluate proteinuria status among diabetic patient with daily tea consumption habits. A descriptive cross sectional design was conducted on 51 DM patient at Bandung Primary Health Center, Tegal City (June-July  2025) who had been diagnosed with DM for at least five years, had a habit of drinking tea, and had no history of kidney stones. Data were collected using a questionnaire on respondents’ characteristics and tea  consumption habits, followed by urine protein examination. Data analysis was performed descrivtively using  frequency distribution. The results shows that the mean age of responden was 58,2 years, with the majority  being female (68,6%) and having lived with DM for 5-9 years ( 60,8%). Black tea was the most frequently  consumed type (86,7%), with more than five years consumption (84,3%) and two cups per day (41,2%) Proteinuria examination revealed 62,7% negative, 23,5% positive 1, 5,9% positive 2, and 7,3% positive 3. The majority of patients with long-term tea consumption had negative proteinuria results, indicating potensial protective effects on kidney function. However, the presence of 37,3% positive proteinuria suggest that other  factors such as glycemic control, duration of diabetes, and variations in the type and intake may still influence  the outcomes.